Peranan Guru Pendidikan Agama Kristen dan Budi Pekerti Melalui Pendekatan Norma Agama dan Perubahan Perilaku dalam Mengatasi Bullying Antar Siswa di SMPN Satu Atap-1 Katingan Tengah - Silvia Rahmelia; Stephanus Prihadi; Nopitha Nopitha (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2023)
Role of Christian religious education teachers is considered strategic in cultivate character and behavior of Christian students as an extension of God's hand in the world whose full of love. However, the current reality is inversely proportional to the bullying phenomena that occur in schools. Bullying among students that occurred at SMPN Satu Atap-1 Katingan Tengah motivated researchers to identify the role of Christian education teachers at that school in overcoming bullying through the approach of religious norms and behavior change. The aims of this research were to identify forms of bullying and describe the role and efforts of teachers in dealing with bullying at SMPN Satu Atap-1 Katingan Tengah. This research uses a qualitative approach with observation, interviews and documentation as data collection techniques. Results proved that the forms of student bullying behavior that occurred at SMPN Satu Atap-1 Katingan Tengah were in the category of verbal and realtion/social bullying. Based on research findings, teachers have carried out roles and efforts such as 1) preparing several students to be appointed as